Rail & Road Revolution in Premier Islamic Bahawalpur State: Bridged the Indus Valley State Railway to the Punjab Railway in British India (Al-Qamar, 2022)
The aim of study to highlight the importance of transportation in North-West part of British India. In order to cater the Defense, Logistic & Strategic Services; East India Company EIC (1612-1857) devised a mega project in Great Indian Peninsula Railway (GIPR). The State BWP; possess Princely status in British India from 1748-1947& it was largest state in top five in Subcontinent. Geographically; BWP State located in Rajasthan Painesville among 18 other Non-Muslim States. It situated in North-West part of British India.  So it was mandatory to connect between Province Sind, State BWP & Provinces of Punjab.  State BWP ruled by twelve Nawabs, who contributed whole heartedly for development & welfare of the Public. Post 1857; a new era begins in State. Nawab adopted modern method of communication & provided the services in Subcontinent. In this regard; State BWP established multiple Railway Lines & Stations. Therefore; British Officers and Engineers were posted in the State. In 1878; a Gigantic Bridge (Empress Bridge) on Sutlej River completed which connected the all-region by Railway Revolution. I have special focus on the North-West part of Railway Communication & highlight the Value & importance of Empress Bridge on Sutlej River.